Sensor development for a nano-satellite - Resham Abdul Razak. (2009)
This report presents the development of a magnetic sensor for use onboard a nano-satellite; it would form one of the modules in the Altitude Determination & Control System (ADCS). The magnetic sensor measures the intensity of magnetic field for the purpose of providing magnetic heading. Through this project, a prototype was assembled and tested on a breadboard level and later, fabricated into a printed circuited board (PCB). The magnetic sensor was developed to create a low cost standard for satellite construction. It is based on Honeywell’s HMC1022, which uses the magnetoresistive technology for magnetic field detection and chosen due to its small size, low power and relatively low cost. The development of the magnetic sensor will be described in stages and how it functions, together with results obtained from the testing are thoroughly explained. Two main analyses were carried out to illustrate the characteristics of the prototype circuit with respect to the HMC1022 characteristics; the orthogonality test and the linearity test. In the orthogonality test, the prototype output voltages are analyzed for a 90° phase difference between the outputs of the HMC1022 sensors. In the linearity test, the sensor sensitivity of the prototype was obtained by referencing the prototype output voltage readings against HMR3000’s magnetic field readings, over a range of ±1 gauss and with the results obtained; a heading formulation was derived to calculate the magnetic heading from a voltage reading. In addition, this report also highlights the challenges and problems encountered by the author in the course of the project and the steps taken to overcome those issues.